Public Benefit and Public Interest – Two Sides of the Same Coin? - Tina Sever (Central European Public Administration Review)
Purpose: Driven by the question of how the concepts of public interest and public benefit differ, this paper delves into the Slovenian legal system. Through an in-depth analysis of legal concepts, national regulations, and case law from the Slovenian Constitutional Court and selected cases from the European Court of Human Rights, its aim is to illuminate the key differences between both terms. Ultimately, the paper seeks to establish fundamental guidelines for understanding the distinct meaning and application of each concept. Design/methodology/approach: The research is based on a content analysis research design, reviewing secondary literature sources. It employs qualitative methods by analysing the relevant theoretical points, rules, and constitutional case law in the Slovenian legal system, as well as selected European Court of Human Rights case law. The analysis focuses on identifying and extracting key theoretical arguments, legal definitions, and practical applications of both concepts. To distinguish between public benefit and public interest, the analysis adopts a comparative approach, examining how each concept is defined, applied, and balanced in different legal contexts. Additionally, synthesis is used to identify commonalities and divergences between different perspectives on these concepts. Finally, conclusions about the relationship between public benefit and public interest are drawn based on the analysed data. Findings: Public interest and public benefit are abstract concepts. The analysis of relevant Slovenian systemic regulations shows that the two are sometimes applied interchangeably. However, theory suggests that there are certain differences in terms of their tangibility and enforceability. Constitutional case law refers to both concepts in a general way without fully defining their content, yet it does not treat them as synonyms. Academic contribution to the field: Public interest and public benefit are central concepts of public administration science. Public interest is key in defining and shaping administrative relations decided in an administrative procedure. It represents the core value of the public sector, ensuring that its operations are legitimate. Public benefit, on the other hand, is the general benefit of an organised wider community, superior to the benefits of individuals and generally considered equivalent to substantive legality. As public and private interests collide, state intervention with appropriate regulation is necessary to protect the public benefit. Originality/significance/value: This research contributes to the understanding of the concepts of public interest and public benefit within the Slovenian legal system and is a novelty in the field as no such overview has been undertaken before. Its value lies in the analysis of Slovenian constitutional case law over the last twenty-two years and insights into European Court of Human Rights case law. The focus on European Court of Human Rights and Slovenian legislation and case law limits the generalisability of the findings to other contexts. This approach was chosen as much of the relevant legislation for this research is independent of EU influences. Nonetheless, being an EU member state, Slovenia’s legal framework shares some commonalities with other European systems. The added value of the analysis lies in its relevance for understanding how these concepts are treated in similar legal systems, offering valuable insights for comparative studies.